Timing of Prenatal Care Initiation and Psychological Wellbeing in Black Women. Issue 6 (November 2020) - Wong, Ana C.; Rengers, Brooke; Nowak, Alexandra L.; Schoeppner, Samantha; Price, Mercedes; Zhang, Liying; Dailey, Rhonda K.; Anderson, Cindy M.; Misra, Dawn P.; Giurgescu, Carmen
Abstract: Purpose: The purpose of this study was to see if timing of prenatal care initiation was related to psychological wellbeing of Black women. Study Design and Methods: Using a cross-sectional design, a sample of 197 pregnant Black women completed a self-reported survey between 8 weeks and less than 30 weeks gestation as part of the Biosocial Impact on Black Births study. The questions asked about the initiation of prenatal care, perceived stress, depressive symptoms, and psychological wellbeing. Multiple linear regression was used to examine if timing of prenatal care initiation was related to psychological variables. Results: Sixty-three women (32%) reported they were not able to initiate their first prenatal care visit as early as they wanted due to various barriers. After adjusting for cofounders, not initiating prenatal care as early as women wanted predicted lower levels of psychological wellbeing. Clinical Implications: Perinatal nurses should assess psychological wellbeing in Black women throughout pregnancy; advocate for Black women who report high levels of stress, psychological distress, or depressive symptoms for further mental health evaluation by their health care provider; and provide resources and education (e.g., support groups, counseling) for these women. Abstract : There are numerous barriers to initiation of prenatal care, some of which may be more prominent among Black women in the United States. In this study, one-third of Black women reported that they did not have their first prenatal visit as early as they wanted. They reported lower levels of psychological wellbeing compared with Black women who initiated prenatal care as early as they wanted. More work is needed on facilitating timely prenatal care for this vulnerable group of mothers.